British blockhouse built by the Hudson Bay Trading Company in 1856 at Fort Colville in Stevens County, Washington, probably between 1900 and 1915 - Palmer, Frank (1900)
PH Coll 1541.9 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number Scanned from a photographic print at 100 dpi in JPEG format at compression rate 3 and resized to 768x512 ppi. 2019